Metode dan Media Pendidikan (Telaah Kajian Hadits Tarbawi) - Saehu Abas (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2021)
Education is a series of activities carried out for the inheritance of the values of science to students. Through education, the values of knowledge and culture can be instilled in students through learning activities. Learning activities can be carried out optimally and structured if educational institutions, educators and students have integration in the success of the direction of learning implementation goals. In the teaching and learning process, two elements that are no less important are teaching methods and learning media. Therefore, it is very important for every educator to understand as well as possible about the learning process of students, so that he can provide guidance and provide an appropriate and balanced learning environment for students. This research uses the library research method. In accordance with the focus discussed, namely